Ultrasonic study of polyethylene glycol and ethanol interactions: impact of concentration and temperature - Niharika Das; Subhraraj Panda; Manoj Kumar Praharaj (Chemical Thermodynamics and Thermal Analysis)
This study examines the molecular interactions between polyethylene glycol (PEG) at concentrations of 5%, 10%, and 15% with ethanol, utilizing ultrasonic techniques across temperatures of 25 °C, 35 °C, 45 °C, and 55 °C. Key acoustic parameters, including Acoustic Impedance (Z), Adiabatic Compressibility (β), Intermolecular Free Length (Lf), Relaxation Time, and Gibbs free energy, were evaluated using the experimental parameters “density (ρ) viscosity (η) and ultrasonic speed (U)”.The analysis focuses on understanding how temperature and concentration variations influence the properties, particularly ultrasonic velocity, density, viscosity, and acoustic parameters, in the PEG-ethanol solution. The findings indicate that higher PEG concentrations enhance molecular interactions, leading to increased acoustic Impedance and decreased adiabatic compressibility and intermolecular free length. As temperature rises, these interactions weaken, resulting in reduced acoustic impedance and altered thermodynamic properties, including an increase in Gibbs free energy. This research offers valuable insights into the thermodynamic and acoustic behavior of PEG-ethanol solutions, contributing to a deeper understanding of their molecular dynamics under varying conditions.